Artistic Polemic with A.P. Chekhov in the Story by T.L. ShchepkinaKupernik “Loneliness” (Proceedings of Southern Federal University. Philology, 2021)
DOI 10.18522/1995-0640-2021-1-10-18From the earliest works, Chekhov acts as a polemicist with both contemporary literature and with the literature of the immediate past. This polemic is expressed not so much in the direct statements of the writer in letters or in conversations recorded by the memory of the memoirists, but in an artistic form, with the help of an imaginative system. However, there were people who polemicized with Chekhov. On the one hand, these were magazine critics, and on the other, fellow writers. One of these authors was T.L. Shchepkina-Kupernik, who wrote the story "Loneliness" at the age of twenty, which was published in the authoritative journal “Russian Thought” in 1894. The works of Chekhov, which caused the greatest resonance among the reading public: “The Jumping Girl”, “Boring Story”, “Ward No. 6”, became the material for the polemic of the young writer. Shchepkina-Kupernik actually agrees with the opinion of the readers who recognized the element of libel in the story "The Jumping girl", and the element of distortions of reality in others. The author of “Loneliness” creates an artistic picture of the world, which seems to her more realistic than Chekhov’s. However, the story of the young writer does not go beyond the bounds of stencil mass literature. All her claims against the author of “Ward No. 6” turn out to be untenable and demonstrate her lack of understanding of the innovative nature of Chekhov’s work. The complex nature of the dialogic character of his works, based on the art of parody stylization, was not perceived by the opponent, who opposed it with a one-dimensional and simplified image of reality.Keywords: artistic polemic, Russian writers, Russian authoresses, literary creativity, stories, artistic picture of the world.